Regulation and function of alternative polyadenylation in development and differentiation - Lorenzo Gallicchio; Gonzalo H. Olivares; Cameron W. Berry; Margaret T. Fuller (RNA Biology)
Alternative processing of nascent mRNAs is widespread in eukaryotic organisms and greatly impacts the output of gene expression. Specifically, alternative cleavage and polyadenylation (APA) is a co-transcriptional molecular process that switches the polyadenylation site (PAS) at which a nascent mRNA is cleaved, resulting in mRNA isoforms with different 3’UTR length and content. APA can potentially affect mRNA translation efficiency, localization, stability, and mRNA seeded protein–protein interactions. APA naturally occurs during development and cellular differentiation, with around 70% of human genes displaying APA in particular tissues and cell types. For example, neurons tend to express mRNAs with long 3’UTRs due to preferential processing at PASs more distal than other PASs used in other cell types. In addition, changes in APA mark a variety of pathological states, including many types of cancer, in which mRNAs are preferentially cleaved at more proximal PASs, causing expression of mRNA isoforms with short 3’UTRs. Although APA has been widely reported, both the function of APA in development and the mechanisms that regulate the choice of 3’end cut sites in normal and pathogenic conditions are still poorly understood. In this review, we summarize current understanding of how APA is regulated during development and cellular differentiation and how the resulting change in 3’UTR content affects multiple aspects of gene expression. With APA being a widespread phenomenon, the advent of cutting-edge scientific techniques and the pressing need for in-vivo studies, there has never been a better time to delve into the intricate mechanisms of alternative cleavage and polyadenylation.